Преобразовать в многочлен: (a-3)(a+-1)^3 2(b+1)(b+4)+(b-6)(b^2+6b+36) 2(u-3)u-(u-3)(u+3) 2(b+2)(b+-1)^3

Gok3004 Gok3004    1   22.07.2019 10:30    2

Ответы
Anna050503 Anna050503  03.10.2020 10:33

(a-3)(a+2)-(a^3-3a^2+3a-1)=a^2+a2-3a-6-a^3+3a+1=4a^2-4a-5-a^3=-a^3+4a^2-4a-52(b+1)(b+4)+(b−6)(b 2 +6b+36)= 

(2b+2)(b+4)+b ^3 +b ^2 6+b36−6b ^2 −36b−216= 

(2b+2)(b+4)+b ^3 +b36−36b−216= (2b+2)(b+4)+b ^3 +36b−36b−216= 

(2b+2)(b+4)+b ^3 −216= 

2b ^2 +8b+2b+8+b ^3 −216= 

2b ^2 +10b−208+b ^3 = b^ 3 +2b^ 2 +10b−208 


ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра